2016
DOI: 10.1080/01694243.2016.1221251
|View full text |Cite
|
Sign up to set email alerts
|

Flexural strength of nano-hybrid resin composite as a function of light attenuation distance and specimen dimension

Abstract: This study evaluated ascending order of light attenuation distance (0,2,4,8 mm) and specimen dimensions (2x2x10, 2x2x12, 2x2x15 mm3) differing from requirements of ISO 4049 (2x2x25 mm3) on the flexural strength of nano-hybrid resin composite. Specimens (N=160) were prepared accordingly and randomly assigned into groups for the factors studied. Specimens were photo-polymerized from increased distances through 1, 2, 3 and 5 overlapping cycles depending on the specimen length after which they were subjected to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Our results were similar to other work that showed curing at 2-or 8-mm using the MCT did not affect the µ-FS 23) . In addition, our results agreed to some extent with another study which reported a significant difference in µ-FS between 2-and 8-mm but not 0-mm of a 2-mm thick nanohybrid composite when cured with a SLED unit 27) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results were similar to other work that showed curing at 2-or 8-mm using the MCT did not affect the µ-FS 23) . In addition, our results agreed to some extent with another study which reported a significant difference in µ-FS between 2-and 8-mm but not 0-mm of a 2-mm thick nanohybrid composite when cured with a SLED unit 27) .…”
Section: Discussionsupporting
confidence: 92%
“…Exploring the effect of curing with the MCT, compared to the CRE, regarding µ-FS when cured at different distances, and with different units, would aid in the understanding of composite clinical performance. Different sample dimensions have been reported when using the µ-FS test 21,27,28) . The specimen dimensions selected in our study were smaller than the active diameter of the light guide tip for the LCUs explored, to allow for one-shot curing 21,27,29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…curing resin-based specimens prepared in accordance with ISO 4049 (25 mm x 2 mm x 2 mm) may receive a non-uniform distribution of energy during the photo-polymerization procedure, which may in turn, affect their flexural strength. Therefore, smaller specimen (10 mm × 2 mm × 2 mm) were used in this study to reduce the variable effect of distance on resin polymerization as described in a previous study[22]. The experimental resin-based materials were inserted into rectangular silicone molds.…”
mentioning
confidence: 99%
“…ISO 4049 stipulates that a specimen should be fabricated with dimensions of 2 mm × 2 mm × 25 mm for the FS test. However, three overlapping irradiation sequences are required to fabricate a specimen with a length of 25 mm due to the smaller diameter of the LCU (10 mm), resulting in nonuniform polymerization [ 39 ]. Therefore, we prepared specimens with dimensions of 2 mm × 2 mm × 8 mm for the FS test in this study, enabling single light curing.…”
Section: Discussionmentioning
confidence: 99%